„Cień Kaina”. Temat wojny w wypowiedziach papieża Franciszka - Okupnik, Małgorzata (Człowiek i Społeczeństwo, 2022)
Christians feel that they should not be indifferent to war, and that it is their duty to react to harm, particularly done to civilians. Catholics expect their greatest authority, the Pope, to have a firm say about war and peace. May people, however, have had the impression that Pope Francis is erratic and assesses the situation in a wrong way. Although he follows the beaten track paved by the Church’s social science and Vatican diplomacy, some of his statements (and things left unsaid) caused and still are causing controversy. The article attempts at understanding the position of Pope Francis. It analyses his utterances regarding war, taken from sources such as the book titled Against War, speeches and social media (Twitter).